B137 When general anesthesia isn't plan a – case report in a patient with idiopathic cardiomyopathy. (11th August 2022) - Baptista, S; Chamusca, R; Duarte, F; Vinagre, J
Abstract : Background and Aims: Cardiac disease represents a challenge to anesthetists, particularly pathologies associated with low ejection fraction. Anesthetic management should focus on preventing intraoperative hypotension and increases in afterload and heart rate, while maintaining adequate levels of anesthesia. Central neuraxial blockade reduces afterload and improves cardiac output but is associated with hypotension. Regional anesthesia is associated with minimal hemodynamic changes while reducing pain and its side effects, namely increased myocardial work and oxygen demand, tachycardia and systemic vascular resistance. Methods: 43 years-old man, scheduled for femoral nailing and tibial osteosynthesis. Past history of idiopathic cardiomyopathy and a diagnosed ejection fraction of 23%, implanted CRT-D, and on the waiting list for a heart transplant. The defibrillating function was disabled preoperatively. Ultrasound guided femoral, obturator and sciatic nerve blocks were performed using ropivacaine 0, 375%. A selective spinal block was performed with 5 mg of bupivacaine. Results: The patient was stable intraoperatively and then admitted to ICU for 24 hours, with an uneventful postoperative recovery. Reported pain management was satisfactory. Conclusions: A patient-centered, individualized anesthetic plan must consider patients' comorbidities. Regional anesthesia plays an essential role in the management of patients with cardiovascular disease, as part of the analgesic plan and as a safer alternative to general anesthesia, avoiding its well-reported side effects. Peripheral nerve blocks can be used together with selective neuraxial blockade, reducing local anesthetic doses and sympathetic blockade.